Atrial Myxoma – An unusual cause of ischemic stroke in young - Sohal, Ravdeep Singh; Shergill, Khushdeep Kaur; Nagi, Gagandeep Singh; Pillai, Hari Janardanan (Autopsy and Case Reports, 2020)
Atrial myxomas are rare primary cardiac tumours with neurological manifestations being reported in 30% of cases. Though a rare cause of ischemic stroke in young patients, considering it as a possibility in absence of any obvious risk factors can help avoid misdiagnosis at early stages. We present a case of left atrial myxoma in a 36-year-old male with no known co-morbidities, showing an unusual clinical presentation of isolated bilateral painless vision loss. With multiple infarcts on Non Contrast Computerised Tomography (NCCT) and a suspicion of Atrial Myxoma on Transesophageal Echocardiography (TEE), patient was successfully managed surgically with confirmation of diagnosis on histopathology.